2018
DOI: 10.4236/jmmce.2018.63022
|View full text |Cite
|
Sign up to set email alerts
|

ANN Based Predictive Modelling of Weld Shape and Dimensions in Laser Welding of Galvanized Steel in Butt Joint Configurations

Abstract: The quality assessment and prediction becomes one of the most critical requirements for improving reliability, efficiency and safety of laser welding. Accurate and efficient model to perform non-destructive quality estimation is an essential part of this assessment. This paper presents a structured and comprehensive approach developed to design an effective artificial neural network based model for weld bead geometry prediction and control in laser welding of galvanized steel in butt joint configurations. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 16 publications
(13 reference statements)
0
2
0
Order By: Relevance
“…Also, it can instantly generate multiple predictive bead images in a few seconds from the given input laser process conditions once training ends, so is very handy as well as practical (one can also share the trained model online, using the open source deep learning libraries such as TensorFlow and PyTorch on GitHub). Note that several approaches [14]- [16] using an artificial neural network (ANN) have been reported in bead shape prediction in laser welding, however, to the best of the authors' knowledge, no deep learning model has been reported yet.…”
Section: Introductionmentioning
confidence: 99%
“…Also, it can instantly generate multiple predictive bead images in a few seconds from the given input laser process conditions once training ends, so is very handy as well as practical (one can also share the trained model online, using the open source deep learning libraries such as TensorFlow and PyTorch on GitHub). Note that several approaches [14]- [16] using an artificial neural network (ANN) have been reported in bead shape prediction in laser welding, however, to the best of the authors' knowledge, no deep learning model has been reported yet.…”
Section: Introductionmentioning
confidence: 99%
“…The Multi-layer feedforward ANN is the most popular and widely used ANN in many applications, especially forecasting, because of their great ability to map nonlinear and complex relationships in multi-inputs multi-output context [11] [12] [13]. Jacques et al proposed an ANN based predictive modelling approach for weld shape and dimensions in butt joint laser welding of galvanized steel [14]. The resulting model presents excellent predictions with an average error less than 10%.…”
Section: Introductionmentioning
confidence: 99%